Edpuzzle-based Interactive Video Media on Basic Dance Movement Material to Improve Student Learning Outcomes - Destia Hera Ramadani; Atip Nurharini (Universitas Pendidikan Ganesha, 2024)
The use of learning media is essential for learning to dance. But teachers still need to use the media to learn to dance. The lack of use of this learning media can affect the students’ learning outcomes, as the study aims to determine. This study aims to assess whether the development of interactive video media based on Edpuzzle, the primary dance movement material in art lessons, can improve student learning outcomes. This research method uses research and development. The model used is ADDIE (Analysis, Design, Development, Implementation, and Evaluation). The source of this research data was obtained from observations, interviews, and questionnaires. The results showed that material experts' feasibility level of Edpuzzle-based interactive video media received a value of 81.25% with feasible criteria, and media experts obtained a value of 95% with very achievable criteria. So, the products developed in this study can be used in learning dance at SD Kota Semarang. Based on the results of media trials, it can improve student learning outcomes. The pre-test and post-test learning results of students in small-scale trials have an N-Gain value of 0.78 with high criteria. While in large-scale trials, get an N-Gain value of 0.77 with high criteria. This research implies that interactive video learning media based on Edpuzzle can improve dance students' learning outcomes. Besides, this media also helps students understand the material, making the learning process more effective.